Pengaruh Ekstrak Limbah Kulit Buah Nanas Cayenne dalam Menurunkan Jumlah Bakteri Coli pada Proses Desinfeksi Air Bersih - P. Irawan, H. Djoko Windu; Karno, Karno; Jayadi, Hurip (Widya Warta, 2014)
The aim of this research is to know closely the effects of the extract of pineapple peels cayenne in killing the bacteria Eschericia coli in the disinfection process of fresh water. The variations of dosages in the research were as follows: treatment 1 : 1000 ml of sampling water intervened by 100 ml of extract of pineapple peels cayenne; treatment 2 : 1000 ml of sampling water intervened by 250 ml of extract of pineapple peels cayenne; treatment 3 : 1000 ml of sampling water intervened by 500 ml of extract of pineapple peels cayenne. The control was sampling water without any intervene of the extract. Each treatment was observed to see the effects of the extract in killing the bacteria Eschericia coli. The result of the literary study, field test, and laboratory test showed the characteristics of extract of pineapple peels cayenne pH : 3,86, the temperature : 29,4 ºC, the humidity : 74,8%, the total sum of acid : 1,71%, organic acid : 0,585, protein : 0,42% and enzyme bromelin : 0.050 – 0.075 unit/ml. The close estimation indicated the total sum of bacteria Eschericia coli in the treatment 1 : 104,6 per 100 ml; in the treatment 2 : 47 per 100 m; in the treatment 3 : 17 per 100 ml, and in the control group : > 2400 per 100 ml. In the treatments 2 and 3 the quality of bacteriology of sampling water already fulfilled the standard of quality as stated in The Regulation of The Health Ministry of Indonesia (Permenkes RI) no. 416/Menkes/Per/IX/1990 about The Standard of Quality of fresh water and drinking water that requires the maximum contents of Eschericia coli = 50 per 100 ml on non-plumbing water. The statistical result of Kruskal Walls Test and t-test proved that there were some effects and different effects among the variations of dosages of the pineapple peels extract cayenne in killing the bacteria Eschericia coli.